The Dataset for Optimal Circulant Topologies - Aleksandr Romanov (Big Data and Cognitive Computing, 2023)
This article presents software for the synthesis of circulant graphs and the dataset obtained. An algorithm and new methods, which increase the speed of finding optimal circulant topologies, are proposed. The results obtained confirm an increase in performance and a decrease in memory consumption compared to the previous implementation of the circulant topologies synthesis method. The developed software is designed to generate circulant topologies for the construction of networks-on-chip (NoCs) and multi-core systems reaching thousands of computing nodes. The developed software makes it possible to achieve high performance on an ordinary research workstation commensurate with similar solutions created for a supercomputer. The use cases of application of the created software for the analysis of routing algorithms in circulants and the regression analysis of the generated dataset of graph signatures to predict the characteristics of graphs of any size are described.